Legion - Dutton, Charles S.; Quaid, Dennis; Tenney, Jon, 1961-; Walsh, Kate, 1967-; Black, Lucas, 1982-; Bettany, Paul, 1971-; Tyrese; Stewart, Scott (Scott Charles); Schink, Peter (Peter R.); Palicki, Adrianne, 1983-; Durand, Kevin; Holland, Willa; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2010)
When God loses his faith in mankind, he sends a legion of angels to bring about Armageddon. An out of the way diner becomes the setting for the ultimate battle of survival as Archangel Michael helps the group of strangers defend themselves and ensure the birth of a baby who will become the new messiah.
DVD release of the 2010 motion picture.
Special features: Creating the Apocalypse-- behind the physical effects; Humanity's Last Line of Defense-- the cast and characters; From Pixels to Picture-- a look at the visual effects.
John Frizzell, music ; Steven Kemper, editor ; John Lindley, director of photography.
Charles S. Dutton, Dennis Quaid, Jon Tenney, Kate Walsh, Lucas Black, Paul Bettany, Tyrese Gibson, Adrianne Palicki, Kevin Durand, Willa Holland.
MPAA rating: R; for strong bloody violence, and language.
DVD ; anamorphic widescreen (2.40:1) presentation ; Dolby digital 5.1 surround.
Keywords: Armageddon -- Drama; Angels -- Drama; Angel films; Action and adventure films; Feature films; Fiction films; Video recordings for the hearing impaired